The Urgency of Food Deregulation in Achieving National Food Security in Indonesia: Legal Reform, Coordinating Governance, and the 2025-2026 Deregulation Agenda - RA Shanti Dewi Mulyaraharjani (Journal of Creative Power and Ambition (JCPA), 2026)
This study analyzes the urgency of food deregulation in Indonesia's pursuit of national food security by examining legal norms, institutional coordination, and recent regulatory reform in 2025-2026. The central problem is that Indonesia's food governance has long been affected by overlapping regulations, fragmented authority, lengthy bureaucracy, high logistics costs, and inconsistent import policy. The revised analysis adds the role of the Coordinating Ministry for Food Affairs as an institutional hub for synchronization, coordination, and policy control in the food sector. It also examines concrete deregulation measures, especially subsidized fertilizer governance through Presidential Regulation No. 6 of 2025 as amended by Presidential Regulation No. 113 of 2025, wider regulatory simplification within the Ministry of Agriculture, import policy reform, and the digitalization of agricultural government assistance. The findings show that deregulation may improve distribution speed, reduce administrative costs, strengthen legal certainty, accelerate self-sufficiency programs, and increase transparency. However, deregulation must remain balanced with state supervision, farmer protection, consumer safety, competition law, environmental sustainability, and food sovereignty principles.